Shiva Linga placed on the floor of a broken temple Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The remains of a foundation of another temple have been discovered within the complex. The temple that once occupied this space consisted of a garbhagriha (sanctum sanctorum) and an antarala (vestibule). Currently, there is a Shiva linga placed on the floor of the garbhagriha.